Reflective Supervision as the Primary Predictor of Improved Nursing Care Documentation Completeness - Yuvita Yuliastanti; Cicilia Ika Wulandari; Sutanto Priyo Hastono (Jurnal Penelitian Kesehatan SUARA FORIKES, 2026)
Nursing care is a series of professional activities aimed at delivering comprehensive services to patients. Nursing care documentation is a critical component of professional nursing practice because it reflects the nurse’s legal and ethical accountability for the interventions provided. In many healthcare settings, documentation completeness remains suboptimal, requiring structured supervisory approaches to improve quality. This study aims to analyze the effectiveness of a reflective supervision model in improving the completeness of nursing care documentation at Hospital X, Kupang. A quantitative approach was employed using a quasi‑experimental pretest–posttest control group design. A total of 60 nurses participated across both groups. Data were collected through direct observation using a validated documentation completeness checklist based on hospital accreditation standards. Statistical analyses included proportion tests, mean difference tests, and logistic regression. Most respondents were female nurses aged 25–35 years, holding a Bachelor’s degree in Nursing and PK II certification. The intervention group showed an improvement in documentation completeness scores from a mean of 23.07 before the intervention to 35.26 after the intervention. There was a significant difference in the proportion of complete documentation between the intervention and control groups (p = 0.000), and a significant increase in the mean documentation score before and after the intervention (p = 0.000). Multivariate analysis indicated that reflective supervision was the main predictor of improved documentation completeness (p = 0.002). In conclusion, reflective supervision is effective in improving the completeness of nursing care documentation. Hospitals should institutionalize reflective supervision as part of routine nursing development programs through director-level decrees or internal nursing policies. Training for ward heads and supervisors is recommended, including 1–2 working days of facilitator preparation covering reflective communication techniques, constructive feedback, and documentation evaluation based on accreditation standards.Keywords: reflective supervision model; nursing care documentation; nurses